Molecular mapping of two loci that confer resistance to Asian rust in soybean - Silva, Danielle C. G. [UNESP]; Yamanaka, Naoki; Brogin, Rodrigo L.; Arias, Carlos A. A.; Nepomuceno, Alexandre L.; Di Mauro, Antonio O. [UNESP]; Pereira, Selma S.; Nogueira, Livia M.; Passianotto, Andre L. L.; Abdelnoor, Ricardo V. (Springer, 2008)
Asian soybean rust (ASR) is caused by the fungal pathogen Phakopsora pachyrhizi Sydow & Sydow. It was first identified in Brazil in 2001 and quickly infected soybean areas in several countries in South America. Primary efforts to combat this disease must involve the development of resistant cultivars. Four distinct genes that confer resistance against ASR have been reported: Rpp1, Rpp2, Rpp3, and Rpp4. However, no cultivar carrying any of those resistance loci has been released. The main objective of this study was to genetically map Rpp2 and Rpp4 resistance genes. Two F(2:3) populations, derived from the crosses between the resistant lines PI 230970 (Rpp2), PI 459025 (Rpp4) and the susceptible cultivar BRS 184, were used in this study. The mapping populations and parental lines were inoculated with a field isolate of P. pachyrhizi and evaluated for lesion type as resistant (RB lesions) or susceptible (TAN lesions). The mapping populations were screened with SSR markers, using the bulk segregant analysis (BSA) to expedite the identification of linked markers. Both resistance genes showed an expected segregation ratio for a dominant trait. This study allowed mapping Rpp2 and Rpp4 loci on the linkage groups J and G, respectively. The associated markers will be of great value on marker assisted selection for this trait.